Trapping fullerenes with jellyfish-like subphthalocyanines - Sanchez-Molina, Irene; Claessens, C. G.; Grimm, Bruno; Guldi, Dirk Michael; Torres, Tomas (Chemical Science, 2013)
Six electronically different concave-shaped subphthalocyanines (SubPcs) have been prepared for testing the structural factors governing fullerenes encapsulation. Thus, the supramolecular interaction of SubPcs with C and C fullerenes in solution has been studied by Job's plot and titration experiments, which yielded quantitative information on both the stoichiometry and strength of the complexes in toluene solution. The importance of the electronic nature of the SubPc was demonstrated, as it influences not only the stability of the complex, but also its stoichiometry. Alkyl chains incorporated in hexaalkylthio-substituted SubPcs seem to in some way cooperate in the binding process and influence its kinetics. In the resulting 2:1 complexes, the large absorption cross section of SubPcs throughout the visible part of the spectrum is the beginning of an unidirectional energy transfer to funnel the excited state energy from the periphery (i.e., two SubPcs) to the core (i.e., C and C). © 2013 The Royal Society of Chemistry.